Tracing the maternal origin of the common wall lizard (Podarcis muralis) on the northern range margin in Central Europe - Jablonski, Daniel; Gvoždík, Václav; Choleva, Lukáš; Jandzik, David; Moravec, Jiří; Mačát, Zdeněk; Veselý, Milan (Mitochondrion, 2019)
The maternal origin of isolated populations of the common wall lizard (Podracis muralis) in the Czech Republic, representing the north-eastern range border of the species, was addressed. We compared mitochondrial DNA sequences of the cytochrome b gene of samples from these populations with those from within the continuous range in Slovakia, the northern Balkan region, and those available from previous studies. We recorded five main haplogroups in the studied region, with all available Central European samples belonging to the same haplogroup. The star-like structure of this haplogroup suggests a scenario of relatively recent, post-glacial population expansion, which is further supported by a coalescent-based demographic analysis. The presence of unique haplotypes in two of the three isolated Czech populations together with close phylogenetic relationships to adjacent Slovak populations suggests either autochthonous origin or human-mediated introductions from geographically and genetically closest populations. We therefore support conservation programs for all three isolated Czech populations.
Keywords: populační růst; Animals; Genetic diversity; cytochromy b; Population Growth; DNA, Mitochondrial; Cytochromes b; Genetic Variation; Conservation; Human-mediated introduction; Male; Czech Republic; Haplotypes; Lizards; mitochondriální DNA; Biogeography; Česká republika; ještěři; zvířata; haplotypy; mužské pohlaví; Climate; genetická variace; Isolated populations